ADAPTIVE WORK CULTURE BASED ON BERAKHLAK VALUES IN THE GOVERNMENT OF WEST JAVA PROVINCE - Arief Rachmat Fauzi; Sri Rejeki Nawangsasih; Rahmat Adriyan US; Helena Fatma Saragih Sitio; Junaidi Sinaga (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
An adaptive work culture is an important aspect of building a bureaucracy that is responsive to change, technological developments, and evolving public demands. The Adaptive value, as part of the BerAKHLAK core values for Indonesian Civil Servants (ASN), emphasizes the ability of civil servants to adjust to change, innovate, and act proactively in addressing various challenges. This study aims to analyze the implementation of an adaptive work culture based on BerAKHLAK values within the Government of West Java Province and to identify the challenges and efforts to strengthen its implementation. This study employs a qualitative approach using a literature review method by examining regulations, government documents, academic literature, and other relevant sources. The findings indicate that the Government of West Java Province has implemented an adaptive work culture through strengthening civil servant competencies, digital transformation, FWA, the development of Sapawarga and Jabar Digital Service, enhanced collaboration, and the implementation of the 2024–2028 Electronic-Based Government System (SPBE) Architecture. These efforts are supported by an increase in the BerAKHLAK Index to 85.4% in 2024, the achievement of the best provincial public service performance, and a “Satisfactory” rating in the SPBE evaluation. However, the internalization of the Adaptive value remains uneven. Key challenges include conventional work cultures, limited innovation-oriented competency development, leadership role modeling, and continuous monitoring. Therefore, strengthening the integration of the Adaptive value into performance management, competency development, leadership, and continuous monitoring and evaluation is necessary.